ANALISIS FILSAFAT ILMU MANAJEMEN PENDIDIKAN : STUDI KASUS PERMASALAHAN FILSAFAT ILMU MANAJEMEN PENDIDIKAN DI WILAYAH HUTAN TROPIS LEMBAB - Della Yulia Putri; Wulandari, Yuli; Yusuf, Ilham; Warman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study critically examines the philosophical underpinnings of education management science in the context of humid tropical forest areas, highlighting the inadequacy of conventional models in addressing the region's unique challenges. This study emphasizes the urgency of developing a contextually relevant, flexible, inclusive, and aligned education management philosophy with environmental sustainability goals. This type of research is qualitative with a literature study data collection technique. Based on the study, it is known that the philosophy of educational management science in humid tropical forest areas faces its own challenges rooted in the tension between modern educational practices and traditional knowledge systems, which is exacerbated by logistical, environmental, and cultural complexities. The root of this problem lies in the epistemological bias of conventional education, historical marginalization, and the pressures of globalization and environmental degradation. To solve this problem, alternative solutions include integrating.